E-Commerce Implementation Training Provides Business Opportunities for the Young Generation in Medan Johor District - Juniarti, Juniarti; Ferine, Kiki Farida; Batubara, Soulthan Saladin (International Conference on Sciences Development and Technology, 2023)
Following the COVID-19 outbreak, using technology to run a business has become essential for all business actors. increased economic expansion along with the arrival of the "digitalization 5.0" era. In the age of digitization, traditional in-person sales must give way to online sales through a variety of e-commerce platforms and marketplaces. The goal of this community service programme is to use e-commerce to improve knowledge and skills. The Medan Johor District Government and community service teams from the surrounding area are among the several stakeholders involved in this endeavour. This time, the service activities include: building strong customer communication and customer commitment applied in the selected firm; teaching e-commerce-based business skills in accordance with motivational direction acquired; and aiming to expand the knowledge of entrepreneurs. The purpose of these activities is to help district inhabitants in Medan, Johor, satisfy their financial demands by increasing their living income.